FADD and TRADD expression and apoptosis in primary hepatocellular carcinoma - Sun, Bao Hua (World J Gastroenterol, 2000)
AIM: To investigate the clinical features of FADD and TRADD expressions in primary hepatocellular carcinoma (HCC) and to determine their relationship with hepatic apoptosis. METHODS: FADD and TRADD expressions were detected by immunohisto chemistry and hepatic apoptosis were determined by in situ end-labeling (ISEL). RESULTS: Ten (25.6%) cases of HCC were detected to express FADD protein. The positive rate in HCC is lower than that in non-cancerous adjacent liver tissues (62.5%) (P ＜ 0.05). In those of grade I-II, 8 (38.1%) cases were FADD positive, while only 2/18 (11.1%) cases of grade III-IV had detectable FADD protein (P ＜ 0.05). No relationship was found between FADD expression and other clinical features, such as gender, age, tumor size, differentiation or metastasis. ISEL positive cells can be seen in all cases of HCC. The hepatic apoptosis was associated with FADD expression as more apoptotic cells were detected in those cases which had moderately to strongly positive FADD, as compared with negative or weak positive FADD cases (P ＜ 0.05). No relationship was found between FADD expression and hepatic apoptosis in non-cancerous adjacent liver tissues. Fifteen of 39 (38.5%) cases of HCC were found positive for TRADD protein, and similar positive rate (37.5%) in non-cancerous adjacent liver tissues (P ＞ 0.05). The expression of TRADD is correlated with HCC differentiation, as only 22.2% of moderately to highly differentiated HCC showed positive TRADD protein, while as high as 52.4% of poorly differentiated HCC had TRADD (P ＜ 0.05). No relationship was found between TRADD expression and gender, age, tumor size or grade or metastasis, although 42.9% of HCC of grade I/II showed positive TRADD which was slightly higher than that of grade III/IV (33.3%, P ＞ 0.05). Hepatic apoptosis was not related to TRADD expression in HCC or non-cancerous adjacent liver tissues. CONCLUSION: Loss of FADD expression plays an important role in HCC carcinogenesis, and expression of TRADD also contributes to HCC development. The cell apoptosis in HCC is associated with FADD expression. However, the expression of TRADD does not correlate well with hepatic apoptosis in HCC.